FROM INNOVATION TO MARKET: INVESTIGATING THE SCALABILITY OF FOOD SMEs IN EMERGING ECONOMIES THROUGH CREATIVE DESTRUCTION - Mujahid; ST. Rukaiyah; Nurmadhani Fitri Suyuthi; Rosnaini Daga; Abdul Samad Arief (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study examines the role of creative destruction in driving the scalability of food SMEs in emerging economies, with a focus on mediating effect of innovation speed and moderating roles of local market adaptation and financial and technical assistance. Data were collected from 373 food SMEs in the Minasamaupata Metropolitan Area of South Sulawesi, Indonesia. The analysis, conducted using PLS-SEM (Partial Least Squares-Structural Equation Modelling), reveals that creative destruction positively impacts both innovation speed and scalability. Moreover, innovation speed mediates relationship between creative destruction and scalability. However, neither local market adaptation nor financial and technical assistance significantly moderated the relationship between creative destruction and scalability. These findings underscore the importance of fostering creative destruction and innovation speed to enhance the growth potential of SMEs in emerging economies. The study contributes to the literature by extending creative destruction and innovation theories to traditional industries in developing regions, with implications for policy and practice